2017
DOI: 10.1016/j.repc.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial dysfunction in light-chain cardiac amyloidosis and hypertrophic cardiomyopathy – A comparative three-dimensional speckle-tracking echocardiographic analysis from the MAGYAR-Path Study

Abstract: Different patterns of LA functional characteristics were demonstrated in AL-CA and HCM patients by 3D-STE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In a recent study, severe LA dysfunction could be demonstrated in AL-CA, therefore the role of LA-RA interactions could also not be excluded. 28 Segmental RA strain analyses showed RA regional differences, suggesting their different contributions to RA (dys)function, as mentioned before (non-uniformity of RA dysfunction). Further studies are needed to confirm our findings in a larger population, comparing results to other diseases with LV hypertrophy as well.…”
Section: Discussionsupporting
confidence: 63%
“…In a recent study, severe LA dysfunction could be demonstrated in AL-CA, therefore the role of LA-RA interactions could also not be excluded. 28 Segmental RA strain analyses showed RA regional differences, suggesting their different contributions to RA (dys)function, as mentioned before (non-uniformity of RA dysfunction). Further studies are needed to confirm our findings in a larger population, comparing results to other diseases with LV hypertrophy as well.…”
Section: Discussionsupporting
confidence: 63%
“…By contrast, echocardiography remains the first-line imaging technique for patients presenting with heart failure, but diagnosis of CA is frequently delayed or missed, due in part to the limited sensitivity and specificity of the wall thickness alone, or wall thickness plus NT-proBNP, as recommended by the current diagnostic criteria. (4,5) Echocardiographic findings that have been proposed for diagnosis of CA range from conventional LV remodelling parameters to those evaluating diastolic function and deformation (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Increased interventricular septum thickness, decreased LV-EF and Doppler velocity E/e’ ratio suggesting abnormal systolic and diastolic LV function could be seen in CA [1] . In recent 3DSTE studies, detailed analysis confirmed significant abnormalities in LV rotational mechanics with 60% ratio of near absence of LV twist (LV ‘rigid body rotation’) [17] with reduced LV strains [18] and enlarged LA volumes and functional deteriorations [19] . Associated with these alterations, MA proved to be dilated and functionally impaired [20] .…”
Section: Discussionmentioning
confidence: 97%